The Influence of Workload and Transformational Leadership Style on Employee Psychological Well-being with Job Satisfaction as a Mediator - Wayan Suryathi, Yayuk Suprihartini, (Program Pascasarjana STIE Amkop Makassar, 2023)
This research explores the intricate relationships among workload, transformational leadership style, job satisfaction, and psychological well-being within the organizational context of PT. Ciputra Residence. Utilizing a sample of 50 employees, the study employs path analysis to examine direct and indirect effects between these key variables. The findings indicate that workload and transformational leadership style significantly influence job satisfaction, which in turn plays a crucial role in shaping the psychological well-being of employees. While workload exhibits a marginal direct effect on psychological well-being, transformational leadership demonstrates a strong direct impact on both job satisfaction and psychological well-being. The study suggests that organizations can optimize employee well-being by strategically managing work demands, fostering transformational leadership practices, and prioritizing initiatives that enhance job satisfaction. These insights contribute to the growing body of knowledge on organizational psychology and provide practical implications for fostering a positive work environment and promoting the holistic well-being of employees. Kata Kunci: Workload, Transformational Leadership Style, Job Satisfaction, Psychological Well-being, Organizational Psychology.